COVID-19 CORONAVIRUS INFECTION IN PATIENTS WITH CARDIOVASCULAR DISEASES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
At the present stage, COVID-19 remains an urgent medical and social health problem worldwide. During the pandemic period, over 765 million cases of COVID-19 were registered, with 6.9 million cases resulting in death. Mortality from infection varies widely depending on the region of residence, age, concomitant conditions, availability of medical care, the level of diagnostic coverage and the system's readiness to provide care to a large number of patients with severe course and ranges from 1 to 5%.
Keywords: COVID-19, coronavirus infection, cardiovascular diseases, arterial hypertension, comorbidity, chronic heart failure, cardiac arrhythmia